Perancangan Sistem Informasi Retensi dan Penyusutan Berkas Rekam Medis di Rumah Sakit - mayang, Selvi; Amirudin , Ahmad; Lestari , Sherly Lestari (Jurnal Sains & Kesehatan, 2024)
The process of retention and shrinkage of medical record files at the South Buton Regency Hospital is still manual, with the current manual system that will certainly hamper the operational activities of the Hospital and can hamper the effectiveness of officer performance. The sorting is reduce the buildop in storing (filing) patient medical records and to reduce the buildup of medical record files which are separated based on their useful value. This is due to limited storage space which means that inactive patient medical record files must be destroyed. Management of medical record files must be kept as well as possible because it is very important for patient care date, accreditation toimprove quality standards in health services, educational research materials, costs and even legal. Therefore, it is necessary to have a retention and shrinkage information system in order to help and facilitate officers in accordance with the conditions and needs of the hospital. This study aims to design an information system for retention and shrinkage of medical record files using Microsoft Access. The method used is to use a descriptive approach and the method of data collection techniques using interview guidelines, observation, documentation studies by analyzing user requirements, making flowchart, DFD level 0-1, and Entity Relationship Diagrams. Respondents in the design of this system involved the head of medical records and medical records officers. The results of this study resulted in a user interface design in the form of a login display, register, dashboard display, medical record display, visit display, retention display and reporting in an integrated manner so that medical services can be interconnected in the hospital. This system design is made in accordance with data collection techniques